Curable composition, cured product, fiber-reinforced composite material, molded product and method for producing the same
By using the method of combining N-(aminoalkyl)piperazine compound with core-shell particles in fiber reinforced composite materials, the problems of insufficient brittleness and impregnation of epoxy resin cured products are solved, and rapid curing and excellent toughness are achieved fiber reinforced composites and molded products.
Patent Information
- Application Number
- CN202080028168.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-23
- Filing Date
- 2020-04-02
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-04-02
AI Technical Summary
In the existing fiber-reinforced composite materials, the cured substance of the epoxy resin is prone to become brittle, resulting in poor impregnation of the reinforced fibers, making it difficult to provide cured substances with excellent strength and toughness in a wider range of applications.
The N-(aminoalkyl)piperazine compound is used as the curing agent for the epoxy resin and used in combination with core-shell particles to form a curable composition with fast curability and toughness.
A curable composition with excellent fast curability and toughness and its fiber-reinforced composite materials and molded products are realized, and the impregnability and mechanical properties of the fiber-reinforced composite materials are improved.
Smart Images

Figure BDA0003298948470000041 
Figure BDA0003298948470000042 
Figure BDA0003298948470000051
Abstract
Description
Technical Field
[0001] The present invention relates to a curable composition having excellent rapid curing properties, high toughness of the cured product, and the like, and a cured product thereof, a fiber-reinforced composite material, a fiber-reinforced resin molded product, and a method for producing the fiber-reinforced resin molded product. Background Art
[0002] Fiber-reinforced composite materials using carbon fibers, aramid fibers, etc. as reinforcing fibers effectively utilize high specific strength and specific elastic modulus and are widely used in general industrial applications such as automobiles and windmills, aerospace industry applications, and sports applications. In recent years, fiber-reinforced composite materials have been actively developed as a lightweight metal.
[0003] As the matrix resin for the fiber-reinforced composite material, thermosetting resins such as unsaturated polyester resins, vinyl ester resins, and epoxy resins are mainly used. Among them, the cured product obtained from the curable composition containing epoxy resin has excellent heat resistance, high strength, high elastic modulus, adhesion, chemical resistance, and good formability, and has been put into practical use as a resin for fiber-reinforced composite materials in various applications.
[0004] On the other hand, epoxy resin for fiber reinforced composite materials has the disadvantage of being easily brittle in cured products compared with other resin systems. In order to develop resins for fiber reinforced composite materials in a wider range of applications, it is required to develop a resin composition that can improve brittleness and provide a cured product with excellent toughness.
[0005] As one of the means for solving the above-mentioned problems, a method of using a modified epoxy resin obtained by preliminarily reacting an epoxy resin with a compound containing a rubber component and a method of adding a toughness-imparting component to the composition have been proposed (for example, see Patent Document 1). However, due to the addition of the toughness-imparting component, the viscosity of the compound (composition) increases, and as a result, the impregnation property into the reinforcing fibers may be deteriorated.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2010-59300 Summary of the invention
[0009] Problems to be solved by the invention
[0010] Therefore, the problem to be solved by the present invention is to provide a curable composition and its cured product, fiber-reinforced composite materials, fiber-reinforced resin molded products, and a method for producing fiber-reinforced resin molded products that are excellent in rapid curing properties, toughness of the cured products, etc., and good impregnation properties into reinforcing fibers.
[0011] Means for solving problems
[0012] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by using an N-(aminoalkyl)piperazine compound as a curing agent for an epoxy resin composition and combining it with core-shell particles, thereby completing the present invention.
[0013] That is, the present invention provides a curable composition characterized by comprising an epoxy resin (A), an amine compound (B) and core-shell particles (C), wherein the amine compound (B) contains an N-(aminoalkyl)piperazine compound (B1) as an essential component.
[0014] The present invention also provides a cured product of the curable composition, a fiber-reinforced composite material using the curable composition, a fiber-reinforced resin molded product, and a method for producing the fiber-reinforced resin molded product.
[0015] Effects of the Invention
[0016] According to the present invention, there can be provided a curable composition excellent in rapid curing properties, toughness of the cured product, and the like, and a cured product thereof, a fiber-reinforced composite material, a fiber-reinforced resin molded product, and a method for producing a fiber-reinforced resin molded product. DETAILED DESCRIPTION
[0017] The curable composition of the present invention is characterized by comprising an epoxy resin (A), an amine compound (B) and core-shell particles (C), wherein the amine compound (B) contains an N-(aminoalkyl)piperazine compound (B1) as an essential component.
[0018] The epoxy resin (A) can be used in various compounds without particular limitation. In addition, the epoxy resin (A) can be used alone or in combination of two or more. As a part of the specific examples of the epoxy resin (A), for example, diglycidyl ether oxybenzene, diglycidyl ether oxynaphthalene, aliphatic epoxy resin, biphenol type epoxy resin, bisphenol type epoxy resin, novolac type epoxy resin, trisphenol methane type epoxy resin, tetraphenol ethane type epoxy resin, phenol or naphthol aralkyl type epoxy resin, phenylene or naphthylene ether type epoxy resin, dicyclopentadiene-phenol addition reaction product type epoxy resin, phenolic hydroxyl-containing compound-alkoxy-containing aromatic compound co-condensation type epoxy resin, glycidylamine type epoxy resin, epoxy resins containing naphthalene skeletons other than these can be cited.
[0019] Examples of the aliphatic epoxy resin include glycidyl ethers of various aliphatic polyol compounds. Examples of the aliphatic polyol compounds include aliphatic diol compounds such as ethylene glycol, propylene glycol, 1,3-propylene glycol, 2-methylpropylene glycol, 1,2,2-trimethyl-1,3-propylene glycol, 2,2-dimethyl-3-isopropyl-1,3-propylene glycol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, and 2,2,4-trimethyl-1,3-pentanediol; and aliphatic polyol compounds having three or more functional groups such as trimethylolethane, trimethylolpropane, glycerol, hexanetriol, pentaerythritol, ditrimethylolpropane, and dipentaerythritol. Among them, glycidyl ethers of the above-mentioned aliphatic diol compounds are preferred because they provide a curable composition having a more excellent mechanical strength of the cured product.
[0020] Examples of the biphenol-type epoxy resin include epoxy resins obtained by polyglycidyl etherifying one or more biphenol compounds such as biphenol and tetramethylbiphenol with epihalohydrin, wherein the epoxy equivalent is preferably in the range of 150 to 200 g / eq.
[0021] Examples of the bisphenol-type epoxy resin include epoxy resins obtained by polyglycidyl etherifying one or more bisphenol compounds such as bisphenol A, bisphenol F, and bisphenol S with epihalohydrin, wherein the epoxy equivalent is preferably in the range of 158 to 200 g / eq.
[0022] Examples of the novolac epoxy resin include epoxy resins obtained by polyglycidyl etherifying a novolac resin containing one or more of various phenolic compounds such as phenol, dihydroxybenzene, cresol, xylenol, naphthol, dihydroxynaphthalene, bisphenol, and biphenol with an epihalohydrin.
[0023] The trisphenol methane type epoxy resin may include, for example, a resin having a structural portion represented by the following structural formula (1) as a repeating structural unit.
[0024] [Chemical formula 1]
[0025]
[0026] [Where R 1 , R 2 Each is independently a hydrogen atom or a point of connection to the structural part represented by the structural formula (1) via a methine group marked with a *. n is an integer greater than or equal to 1.]
[0027] Examples of the phenol or naphthol aralkyl epoxy resin include epoxy resins having a molecular structure in which glycidyloxybenzene or glycidyloxynaphthalene structures are linked at a structural site represented by any of the following structural formulas (2-1) to (2-3).
[0028] [Chemical formula 2]
[0029]
[0030] (In the formula, X is any one of an alkylene group having 2 to 6 carbon atoms, an ether bond, a carbonyl group, a carbonyloxy group, a sulfide group, and a sulfone group.]
[0031] Examples of the glycidylamine type epoxy resin include N,N-diglycidylaniline, 4,4'-methylenebis[N,N-diglycidylaniline], triglycidylaminophenol, and N,N,N',N'-tetraglycidylxylenediamine.
[0032] As an example of the epoxy resin containing a naphthalene skeleton, a bis(hydroxynaphthalene) type epoxy resin represented by any of the following structural formulas (3-1) to (3-3) can be mentioned.
[0033] [Chemical formula 3]
[0034]
[0035] Among the epoxy resins (A), from the perspective of forming a curable composition with excellent balance between heat resistance and mechanical strength of the cured product, it is preferred to use any of aliphatic epoxy resins, bisphenol epoxy resins, trisphenol methane epoxy resins, glycidylamine epoxy resins, and bis(hydroxynaphthalene) epoxy resins shown in any of the above structural formulas (3-1) to (3-3). Among them, bisphenol epoxy resins are particularly preferred, and 40% by mass or more is preferably used relative to the total mass of the epoxy resin (A). In addition, from the perspective of better heat resistance and mechanical strength of the cured product, it is preferred to use the bisphenol epoxy resin and aliphatic epoxy resin in combination. At this time, the mass ratio of the bisphenol epoxy resin to the aliphatic epoxy resin is preferably in the range of 70 / 30 to 99 / 1. In addition, when the aliphatic epoxy resin is used, the ratio of the aliphatic epoxy resin to the total mass of the epoxy resin (A) is preferably in the range of 1 to 30% by mass. When the trisphenol methane type epoxy resin is used, it is preferably used in an amount of 5 to 50% by mass relative to the total mass of the epoxy resin (A). When the glycidylamine type epoxy resin is used, it is preferably used in an amount of 5 to 50% by mass relative to the total mass of the epoxy resin (A). When the bis(hydroxynaphthalene) type epoxy resin is used, it is preferably used in an amount of 1 to 30% by mass relative to the total mass of the epoxy resin (A).
[0036] In addition, particularly when used as a fiber-reinforced composite material described later, from the viewpoint of the curability, fluidity, and impregnation into reinforcing fibers of the composition, the epoxy equivalent of the epoxy resin (A) is preferably in the range of 165 to 190 g / eq and the viscosity at 25° C. is in the range of 2000 to 11000 mPa·s.
[0037] The amine compound (B) is used as a curing agent or curing accelerator for the epoxy resin (A). In the present invention, the amine compound (B) contains an N-(aminoalkyl)piperazine compound (B1) as an essential component.
[0038] Examples of the N-(aminoalkyl)piperazine compound (B1) include compounds represented by the following structural formula (4).
[0039] [Chemical formula 4]
[0040]
[0041] [Where R 3 is an alkylene group, R 4 is a hydrogen atom or an alkyl group. 5 A hydrogen atom or -R 3 -NR 4 2.]
[0042] In the above structural formula (4), R 3 The alkylene group shown may be a straight chain or a branched chain. In addition, the number of carbon atoms is not particularly limited. In view of forming a curable composition having excellent heat resistance and mechanical strength in the cured product and excellent rapid curing properties, R 3 An alkylene group having 1 to 6 carbon atoms is preferred, and a linear alkylene group having 1 to 6 carbon atoms is more preferred.
[0043] In the above structural formula (4), R 4 is a hydrogen atom or an alkyl group. The alkyl group may be a straight chain or a branched chain. In addition, the number of carbon atoms is not particularly limited. In view of the fact that the cured product has excellent heat resistance and mechanical strength and also excellent rapid curing properties, R 4 It is preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and more preferably a hydrogen atom.
[0044] In the above structural formula (4), R 5 A hydrogen atom or -R 3 -NR 4 2. Among them, from the perspective of forming a curable composition having excellent heat resistance and mechanical strength of the cured product and excellent rapid curing properties, R5 More preferably, it is a hydrogen atom.
[0045] In the present invention, as the above-mentioned amine compound (B), other amine compounds other than the N-(aminoalkyl)piperazine compound (B1) may be used in combination. In the present invention, from the aspect of fully exerting the excellent effect of heat resistance and mechanical strength of the cured product, the ratio of the above-mentioned N-(aminoalkyl)piperazine compound (B1) to the total mass of the amine compound (B) is preferably in the range of 20 to 80 mass %.
[0046] Examples of other amine compounds include aliphatic amine compounds (B2) such as ethylenediamine, N,N,N',N'-tetramethylethylenediamine, propylenediamine, N,N,N',N'-tetramethylpropylenediamine, dimethylaminopropylamine, diethylaminopropylamine, dibutylaminopropylamine, diethylenetriamine, N,N,N',N",N"-pentamethyldiethylenetriamine, triethylenetetramine, tetraethylenepentamine, 3,3'-diaminodipropylamine, butanediamine, pentanediamine, hexanediamine, trimethylhexanediamine, N,N,N',N'-tetramethylhexanediamine, bis(2-dimethylaminoethyl)ether, dimethylaminoethoxyethoxyethanol, triethanolamine, dimethylaminohexanol, and 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro(5,5)undecane adduct;
[0047] Amine compounds (B3) having a polyoxyalkylene structure in the molecular structure, such as polyoxyethylenediamine and polyoxypropylenediamine;
[0048] Alicyclic amine compounds (B4) such as cyclohexylamine, dimethylaminocyclohexane, menthanediamine, isophoronediamine, norbornenediamine, bis(aminomethyl)cyclohexane, diaminodicyclohexylmethane, and methylenebis(methylcyclohexaneamine);
[0049] Heterocyclic amine compounds (B5) such as pyrrolidine, piperidine, piperazine, N,N'-dimethylpiperazine, morpholine, methylmorpholine, ethylmorpholine, quinuclidine (1-azabicyclo[2.2.2]octane), triethylenediamine (1,4-diazabicyclo[2.2.2]octane), pyrrole, pyrazole, pyridine, hexahydro-1,3,5-tris(3-dimethylaminopropyl)-1,3,5-triazine, and 1,8-diazabicyclo-[5.4.0]-7-undecene;
[0050] Aromatic ring-containing amine compounds (B6) such as phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, N-methylbenzylamine, N,N-dimethylbenzylamine, diethyltoluenediamine, benzylenediamine, α-methylbenzylmethylamine, and 2,4,6-tris(dimethylaminomethyl)phenol;
[0051] imidazole, 1-methylimidazole, 2-methylimidazole, 3-methylimidazole, 4-methylimidazole, 5-methylimidazole, 1-ethylimidazole, 2-ethylimidazole, 3-ethylimidazole, 4-ethylimidazole, 5-ethylimidazole, 1-n-propylimidazole, 2-n-propylimidazole, 1-isopropylimidazole, 2-isopropylimidazole, 1-n-butylimidazole, 2-n-butylimidazole, 1-isobutylimidazole, 2-isobutylimidazole, 2-undecyl-1H-imidazole, 2-heptadecyl-1H-imidazole, 1,2-dimethylimidazole, 1,3-dimethylimidazole, 2,4-dimethylimidazole, 2-ethyl-4-methylimidazole, 1-phenylimidazole, 2-phenyl-1H-imidazole, 4-methyl-2-phenyl-1H-imidazole, 2 imidazole compounds (B7) such as phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-phenylimidazole isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-cyanoethyl-2-phenyl-4,5-bis(2-cyanoethoxy)methylimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, and 1-benzyl-2-phenylimidazole hydrochloride;
[0052] Imidazolidine compounds (B8) such as 2-methylimidazoline and 2-phenylimidazoline, and the like.
[0053] Among these other amine compounds, the aliphatic amine compound (B2) is preferably used, and triethylenetetramine is more preferred. When the aliphatic amine compound (B2) is used, the mass ratio [(B1) / (B2)] to the N-(aminoalkyl)piperazine compound (B1) is preferably in the range of 20 / 80 to 80 / 20.
[0054] In addition, in terms of further excellent heat resistance and mechanical strength in the cured product, it is preferred to use an alicyclic amine compound (B4). In addition, from the perspective of forming a curable composition having excellent heat resistance and mechanical strength in the cured product and excellent rapid curing properties, compounds in which an alicyclic structure and an amino group are bonded via an alkylene group, such as norbornene diamine and bis(aminomethyl)cyclohexane, are more preferred. When an alicyclic amine compound (B4) is used, the mass ratio [(B1) / (B4)] to the above-mentioned N-(aminoalkyl)piperazine compound (B1) is preferably in the range of 20 / 80 to 80 / 20.
[0055] In the curable composition of the present invention, the mixing ratio of the epoxy resin (A) and the amine compound (B) is not particularly limited and can be appropriately adjusted according to the desired performance and application of the cured product. As an example of mixing, a method of mixing in a ratio in the range of 0.5 to 1.05 mol relative to 1 mol of epoxy groups in the epoxy resin (A) and the total number of moles of active hydrogen in the amine compound (B) can be cited.
[0056] When a tertiary amine, the above-mentioned imidazole compound or the imidazoline compound is used as the above-mentioned amine compound (B), it is preferably blended in a ratio of 0.01 to 10% by mass based on the total mass of the curable composition.
[0057] In the present invention, other curing agents or curing accelerators (B') may be used together with the above-mentioned amine compound (B). Other curing agents or curing accelerators (B') may use any of various compounds generally used as curing agents or curing accelerators for epoxy resins. Specifically, examples include anhydrides such as tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylendophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylnadic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and maleic anhydride;
[0058] Dicyandiamide, or an amide compound obtained by reacting a carboxylic acid compound such as an aliphatic dicarboxylic acid such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, a fatty acid, a dimer acid, with the above-mentioned amine compound (B);
[0059] Phenol, dihydroxybenzene, trihydroxybenzene, naphthol, dihydroxynaphthalene, trihydroxynaphthalene, anthracenol, dihydroxyanthracene, trihydroxyanthracene, biphenol, bisphenol, and compounds containing phenolic hydroxyl groups having one or more of the following substituents on their aromatic nuclei: aliphatic hydrocarbon groups such as methyl, ethyl, vinyl, propyl, butyl, pentyl, hexyl, cyclohexyl, heptyl, octyl, and nonyl; alkoxy groups such as methoxy, ethoxy, propoxy, and butoxy; halogen atoms such as fluorine, chlorine, and bromine; phenyl, naphthyl, anthracenyl, and aryl groups substituted with the above aliphatic hydrocarbon groups, alkoxy groups, halogen atoms, etc. on their aromatic nuclei; phenylmethyl, phenylethyl, naphthylmethyl, naphthylethyl, and aralkyl groups substituted with the above aliphatic hydrocarbon groups, alkoxy groups, halogen atoms, etc. on their aromatic nuclei;
[0060] Phenolic resins such as phenolic resins of the phenolic hydroxyl group-containing type, trisphenol methane type, tetraphenol ethane type, phenol or naphthol aralkyl type, phenylene or naphthylene ether type, dicyclopentadiene-phenol addition reaction product type, phenolic resins of the phenolic hydroxyl group-alkoxy group-containing aromatic compound co-condensation type, etc.;
[0061] Urea compounds such as p-chlorophenyl-N,N-dimethylurea, 3-phenyl-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-N,N-dimethylurea, and N-(3-chloro-4-methylphenyl)-N',N'-dimethylurea;
[0062] Phosphorus compounds; metal salts of organic acids; Lewis acids; amine complex salts, etc.
[0063] The mixing ratio of other curing agents or curing accelerators (B') can be appropriately adjusted according to the desired performance and use of the cured product, and is preferably used in the curable composition in the range of 0.5 to 30% by mass. Among the above-mentioned other curing agents or curing accelerators (B'), the above-mentioned phenolic hydroxyl-containing compounds and phenolic resins are preferred from the aspects of rapid curing, heat resistance in the cured product, and excellent mechanical strength of the curable composition. The hydroxyl equivalent of the phenolic resin is preferably in the range of 100 to 300 g / equivalent. The mixing ratio of the above-mentioned phenolic hydroxyl-containing compounds and phenolic resins can be appropriately adjusted according to the desired performance and use of the cured product, and is preferably used in the curable composition in the range of 0.5 to 30% by mass, and more preferably in the range of 0.5 to 10% by mass.
[0064] The mixing ratio of the epoxy resin (A), the amine compound (B), and other curing agents or curing accelerators (B') is not particularly limited and can be appropriately adjusted according to the desired performance and application of the cured product. As an example, the following method can be cited: relative to 1 mol of epoxy groups in the epoxy resin (A), the total molar number of curable functional groups in the amine compound (B) and other curing agents or curing accelerators (B') is mixed in a ratio in the range of 0.5 to 1.05 mol.
[0065] The core-shell particles (C) used in the present invention are preferably copolymers consisting of a core layer of a first (co)polymer and a shell layer formed by graft polymerization thereon of a second (co)polymer. The shell layer can cover a part or the entirety of the surface of the core portion by graft polymerization of the monomers constituting the graft component in the presence of the core component. In addition, the core-shell particles (C) can be composed of a two-layer structure or a multilayer structure comprising more than three layers.
[0066] From the aspect of effectively improving the mechanical strength, especially the fracture toughness of the cured product, the core portion is preferably composed of a copolymer with an elastomer or a rubbery copolymer as the main component. The (co)polymer constituting the core portion preferably has the properties of a rubber, so the glass transition temperature is preferably below 0°C, more preferably below -20°C.
[0067] Preferred specific examples of the core portion include butadiene rubber, butadiene-styrene rubber, butadiene alkyl acrylate rubber, alkyl acrylate rubber, and organosilicone rubber.
[0068] The number average particle size of the core part is preferably 20 to 600 nm, and more preferably 30 to 400 nm from the viewpoint of effective toughness improvement. The number average particle size of the core part can be measured using Microtrac UPA150 (manufactured by Nikkiso Co., Ltd.).
[0069] The core-shell particles (C) are obtained by polymerizing one or more vinyl monomers in the presence of the core to form a shell layer. The core-shell copolymer can be prepared, for example, by emulsion polymerization, suspension polymerization, microsuspension polymerization, etc., and is preferably prepared by emulsion polymerization from the viewpoint of particle size control.
[0070] The core-shell particles (C) preferably comprise a core portion of a rubber polymer of preferably 50 to 97% by mass, more preferably 70 to 90% by mass, and a shell layer of a polymer of a vinyl monomer of preferably 3 to 50% by mass, more preferably 10 to 30% by mass. The shell layer is preferably chemically bonded to at least one side of the polymer chain of at least 70% or more, more preferably 90% or more, and further preferably 95% or more, with respect to the core portion.
[0071] From the aspect that it is easy to maintain the core-shell structure even after forming a solidified product, the core-shell particles (C) preferably have a cross-linked structure at least partially in the core. In the case of having a cross-linked structure, a solvent-insoluble component is included. In order to observe the degree of cross-linking, the amount of solvent-insoluble matter (i.e., gel fraction) of the core-shell particles can be measured. In the measurement, the sample is immersed in an excess of methyl ethyl ketone (MEK) at room temperature for 24 hours, and then centrifuged at 12,000 rpm for 1 hour, thereby removing the soluble component together with the solvent, and measuring the mass of the residual MEK insoluble matter, as the ratio of the residual sample mass at this time to the input sample mass, expressed in mass%. Partially having a cross-linked structure means that the mass % is less than 100%. From the viewpoint of obtaining excellent performance balance, the amount of solvent-insoluble components is preferably 80 to 100 mass %, more preferably 90 to 100 mass %.
[0072] As the vinyl monomer constituting the shell layer, for example, there can be mentioned aromatic vinyl monomers such as styrene, α-methylstyrene, p-methylstyrene, and divinylbenzene; cyanide vinyl monomers such as acrylonitrile or methacrylonitrile; alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate; glycidyl vinyl monomers such as glycidyl (meth)acrylate and glycidyl vinyl ether; hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate and hydroxybutyl (meth)acrylate; vinyl derivatives containing alicyclic epoxy groups such as 4-vinylcyclohexene 1,2-epoxide and epoxycyclohexene (meth)acrylate; vinyl derivatives containing oxetane groups such as 2-oxetanylpropyl (meth)acrylate; divinyl monomers such as ethylene glycol di(meth)acrylate and 1,3-butylene glycol di(meth)acrylate, etc. The above vinyl monomers may be used alone or in combination of two or more.
[0073] From the viewpoint of reactivity with the core part, it is preferred that the shell layer contains at least one reactive functional group selected from the group consisting of an epoxy group, a carboxyl group, a hydroxyl group, and an amino group.
[0074] The core-shell particles (C) are well dispersed in the curable resin composition of the present invention relative to the matrix phase mainly composed of the epoxy resin (A), for example, dispersed in a slow aggregation state in which an average of 10 or less primary particles of the core-shell particles (C) are aggregated per dispersed phase, which is preferred in terms of exhibiting excellent fracture toughness in the cured product.
[0075] In the curable resin composition of the present invention, the core-shell particles (C) are preferably dispersed independently of the matrix phase containing the epoxy resin (A) as the main component, because the cured product exhibits better fracture toughness. Therefore, it is preferred to use the core-shell particles (C) in advance in the form of primary particles dispersed in the epoxy resin (A) without agglomeration. In this case, it is more preferred to disperse the primary particles in a range of 30 to 1000 nm in average particle size.
[0076] The epoxy resin dispersed with the core-shell particles (C) can be obtained using the method described in the prior art (for example, U.S. Patent No. 4778851). In addition, from the viewpoint of making the core-shell co-particles (C) of the present invention easily dispersed in the epoxy resin in the state of primary particles, and from the viewpoint of manufacturing an epoxy resin dispersed with core-shell particles at a high speed and inexpensively to the extent that industrial production is possible, it is preferably subjected to the following steps. That is, it is a method for preparing by the following steps: a first step of obtaining a dispersion of core-shell particles containing a specific organic solvent; a second step of adding an epoxy resin to the dispersion to obtain an epoxy resin dispersed with core-shell particles; and a third step of removing the above-mentioned specific organic solvent from the epoxy resin dispersed with core-shell particles. Such a method is described, for example, in Japanese Patent Laid-Open No. 2013-241479.
[0077] In addition, examples of core-shell particles (C) that can be obtained as commercial products include "MetaBlen" (manufactured by Mitsubishi Chemical Co., Ltd.), "Stafyloid" (manufactured by AICA Industries, Ltd.), and "Paraloid" (manufactured by Dow Chemical Co., Ltd.). Examples of epoxy resins in which core-shell particles are dispersed include "Kaneace" (manufactured by Kaneka Co., Ltd.), "Acryset BP Series" (manufactured by Nippon Shokubai Co., Ltd.), and the like. It is preferred to use epoxy resins in which core-shell particles are dispersed because it is possible to shorten the preparation time of the composition and to improve the dispersion state of the rubber particles in the composition.
[0078] In the curable composition of the present invention, the content of the core-shell particles (C) is preferably in the range of 0.5 to 10% by mass relative to the total mass of the epoxy resin (A), the amine compound (B) and the core-shell particles (C) from the viewpoint of the toughness of the obtained cured product, and is particularly preferably in the range of 2 to 7% by mass from the viewpoint of better balance of the fluidity, rapid curing property and performance of the cured product of the curable composition.
[0079] The curable composition of the present invention may contain other components in addition to the epoxy resin (A), the amine compound (B), the other curing agent or curing accelerator (B') and the core-shell particles (C). Examples of other components include acid-modified polybutadiene, polyethersulfone resin, polycarbonate resin, polyphenylene ether resin, acrylic resin, etc.
[0080] The acid-modified polybutadiene is a component reactive with the epoxy resin (A). By using the acid-modified polybutadiene in combination, the obtained cured product can exhibit excellent mechanical strength, heat resistance, and moist heat resistance.
[0081] Examples of the acid-modified polybutadiene include those having a skeleton derived from 1,3-butadiene or 2-methyl-1,3-butadiene in the butadiene skeleton. Examples of the substance derived from 1,3-butadiene include those having any structure of 1,2-vinyl type, 1,4-trans type, 1,4-cis type, and those having two or more of these structures. Examples of the substance derived from 2-methyl-1,3-butadiene include those having any structure of 1,2-vinyl type, 3,4-vinyl type, 1,4-cis type, 1,4-trans type, and those having two or more of these structures.
[0082] The acid-modified component of the acid-modified polybutadiene is not particularly limited, and unsaturated carboxylic acids may be mentioned. Preferred unsaturated carboxylic acids include acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, and itaconic anhydride. From the perspective of reactivity, itaconic anhydride and maleic anhydride are preferred, and maleic anhydride is more preferred.
[0083] Regarding the content of unsaturated carboxylic acid in the above-mentioned acid-modified polybutadiene, from the viewpoint of reactivity with the above-mentioned epoxy resin (A), when the acid-modified polybutadiene is composed of a substance derived from 1,3-butadiene, its acid value is preferably 5 mgKOH / g to 400 mgKOH / g, more preferably 20 mgKOH / g to 300 mgKOH / g, and further preferably 50 mgKOH / g to 200 mgKOH / g. In addition, the unsaturated carboxylic acid component can be copolymerized in the acid-modified polybutadiene, and its form is not limited. For example, random copolymerization, block copolymerization, graft copolymerization (graft modification), etc. can be cited. The weight average molecular weight (Mw) of the acid-modified polybutadiene is preferably in the range of 1000 to 100000.
[0084] Acid-modified polybutadiene is obtained by modifying polybutadiene with unsaturated carboxylic acid, and commercial products can be used directly. Commercial products include, for example, maleic anhydride-modified liquid polybutadiene (polyvest MA75, Polyvest EPMA120, etc.) manufactured by Evonik Degussa, and maleic anhydride-modified polyisoprene (LIR-403, LIR-410) manufactured by Kuraray.
[0085] The content of the acid-modified polybutadiene in the curable composition is preferably 1 to 40 parts by mass, more preferably 3 to 30 parts by mass, based on 100 parts by mass of the total mass of the resin components of the curable composition, from the viewpoint that the elongation, heat resistance, and moisture-heat resistance of the resulting cured product become good.
[0086] The polyethersulfone resin is a thermoplastic resin and is not included in the crosslinking network in the curing reaction of the curable composition. However, due to the excellent modifier effect having a high Tg, the obtained cured product can exhibit more excellent mechanical strength and heat resistance.
[0087] The content of the polyethersulfone resin in the curable composition is preferably 1 to 30 parts by mass, more preferably 3 to 20 parts by mass, based on 100 parts by mass of the total mass of the resin components of the curable composition, from the viewpoint that the mechanical strength and heat resistance of the obtained cured product become good.
[0088] Examples of the polycarbonate resin include polycondensates of divalent or difunctional phenol and halogenated carbonyl, and polycarbonate resins obtained by polymerizing divalent or difunctional phenol and carbonic acid diester by an ester exchange method.
[0089] Examples of the above-mentioned divalent or difunctional phenol include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)ketone, hydroquinone, resorcinol, catechol, etc. Among these divalent phenols, bis(hydroxyphenyl)alkanes are preferred, and 2,2-bis(4-hydroxyphenyl)propane as the main raw material is particularly preferred.
[0090] On the other hand, examples of the halogenated carbonyl or carbonic acid diester that reacts with divalent or difunctional phenols include phosgene; diaryl carbonates such as dihalogenated formates of dihydric phenols, diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, and m-tolyl carbonate; and aliphatic carbonate compounds such as dimethyl carbonate, diethyl carbonate, diisopropyl carbonate, dibutyl carbonate, dipentyl carbonate, and dioctyl carbonate.
[0091] In addition, the above-mentioned polycarbonate resin may have a branched structure in addition to a linear structure of the molecular structure of the polymer chain. Such a branched structure can be introduced by using 1,1,1-tris(4-hydroxyphenyl)ethane, α,α',α"-tris(4-hydroxyphenyl)-1,3,5-triisopropylbenzene, phloroglucinol, trimellitic acid, indolequinone bis(o-cresol) and the like as raw material components.
[0092] Examples of the polyphenylene ether resin include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-ethyl-6-n-propyl-1,4-phenylene) ether, poly(2,6-di-n-propyl-1,4-phenylene) ether, poly(2-methyl-6-n-butyl-1,4-phenylene) ether, poly(2-ethyl-6-isopropyl-1,4-phenylene) ether, and poly(2-methyl-6-hydroxyethyl-1,4-phenylene) ether.
[0093] Among them, poly(2,6-dimethyl-1,4-phenylene) ether is preferred, and polyphenylene ether containing 2-(dialkylaminomethyl)-6-methylphenylene ether units, 2-(N-alkyl-N-phenylaminomethyl)-6-methylphenylene ether units, etc. as partial structures may also be used.
[0094] The above-mentioned polyphenylene ether resin may be a modified polyphenylene ether resin into which reactive functional groups such as carboxyl, epoxy, amino, mercapto, silyl, hydroxyl, dicarboxylic anhydride, etc. are introduced into the resin structure by any method such as graft reaction or copolymerization, within the scope not impairing the purpose of the present invention.
[0095] The acrylic resin may be added for the purpose of improving the mechanical strength, particularly the fracture toughness, of the cured product.
[0096] The constituent monomers and polymerization methods of the acrylic resin are appropriately selected according to the desired performance. As a part of the specific examples of the constituent monomers, there can be cited alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; (meth)acrylates having alicyclic structures such as cyclohexyl (meth)acrylate and cyclohexyl methacrylate; (meth)acrylates having aromatic rings such as benzyl (meth)acrylate; (fluoro)alkyl (meth)acrylates such as 2-trifluoroethyl (meth)acrylate; (meth)acrylic acid, (anhydride) maleic acid, maleic anhydride and other acid group-containing monomers; (meth)acrylic acid hydroxyethyl, (meth)acrylate hydroxypropyl, (meth)acrylate hydroxybutyl; (meth)acrylate glycidyl, 3,4-epoxycyclohexyl methyl methacrylate and other epoxy group-containing monomers; aromatic vinyl compounds such as styrene; diene compounds such as butadiene and isoprene, etc. Among them, acrylic resins containing alkyl (meth)acrylate as a main component are preferred because they provide a curable composition having further excellent mechanical strength in the cured product.
[0097] The acrylic resin is preferably a block copolymer formed by copolymerization of multiple block polymers composed of different monomers. As block copolymers, AB-type diblock type, ABA-type or ABC-type triblock type, etc. can be cited. Among them, from the perspective of a curable composition having a further excellent mechanical strength of a cured product, it is preferred to have both a block with methyl (meth)acrylate as the main component and a block with butyl (meth)acrylate as the main component. More specifically, a triblock acrylic resin comprising a polymethyl methacrylate block-polybutyl acrylate block-polymethyl methacrylate block, a diblock acrylic resin comprising a polymethyl methacrylate block-polybutyl acrylate block, and a diblock acrylic resin are particularly preferred. The weight average molecular weight (Mw) of the acrylic resin is preferably in the range of 1000 to 500000.
[0098] The content of the acrylic resin in the curable composition is not particularly limited and can be appropriately adjusted according to the desired cured product performance, etc. Among them, from the perspective of a curable composition having a further excellent mechanical strength in a cured product, when the total mass of the resin components of the curable composition is 100 parts by mass, the range is preferably 0.1 to 20 parts by mass, and more preferably 0.5 to 10 parts by mass.
[0099] The curable composition of the present invention can contain flame retardant / flame retardant auxiliary, filling material, additive, organic solvent etc. within the scope of not damaging the effect of the present invention. The order of coordination during manufacturing the curable composition is not particularly limited as long as it is a method that can achieve the effect of the present invention. That is, all components can be pre-mixed and used, or they can be appropriately mixed and used in sequence. In addition, the coordination method can be, for example, mixed using mixing machines such as extruders, heating rollers, kneaders, roller mixers, Banbury mixers, etc. Mixing is manufactured. Hereinafter, various components that can be contained in the curable composition of the present invention are described.
[0100] Flame retardant / flame retardant additive
[0101] The curable composition of the present invention may contain a non-halogen flame retardant containing substantially no halogen atoms in order to exhibit flame retardancy.
[0102] As the above-mentioned non-halogen flame retardant, for example, phosphorus flame retardants, nitrogen flame retardants, silicone flame retardants, inorganic flame retardants, organic metal salt flame retardants, etc. can be mentioned. There is no limitation in using them. They can be used alone or multiple flame retardants of the same series can be used. In addition, flame retardants of different series can be used in combination.
[0103] As the phosphorus flame retardant, any inorganic or organic flame retardant may be used. Examples of the inorganic compound include red phosphorus, ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate, and inorganic nitrogen-containing phosphorus compounds such as phosphoric acid amide.
[0104] In addition, for the purpose of preventing hydrolysis, etc., the above-mentioned red phosphorus is preferably subjected to surface treatment. Examples of the surface treatment method include: (i) a coating treatment method using an inorganic compound such as magnesium hydroxide, aluminum hydroxide, zinc hydroxide, titanium hydroxide, bismuth oxide, bismuth hydroxide, bismuth nitrate or a mixture thereof; (ii) a coating treatment method using a mixture of an inorganic compound such as magnesium hydroxide, aluminum hydroxide, zinc hydroxide, titanium hydroxide and a thermosetting resin such as a phenolic resin; (iii) a double coating treatment method using a thermosetting resin such as a phenolic resin on a film of an inorganic compound such as magnesium hydroxide, aluminum hydroxide, zinc hydroxide, titanium hydroxide, etc.
[0105] Examples of the above-mentioned organophosphorus compounds include general-purpose organophosphorus compounds such as phosphate compounds, phosphonic acid compounds, phosphinate compounds, phosphine oxide compounds, phosphorane compounds, and organic nitrogen-containing phosphorus compounds; and cyclic organophosphorus compounds such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydrooxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(2,7-dihydrooxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide.
[0106] When the phosphorus-based flame retardant is used, hydrotalcite, magnesium hydroxide, a boron compound, zirconium oxide, a black dye, calcium carbonate, zeolite, zinc molybdate, activated carbon, or the like may be used in combination with the phosphorus-based flame retardant.
[0107] Examples of the nitrogen-based flame retardant include triazine compounds, cyanuric acid compounds, isocyanuric acid compounds, and phenothiazine, and triazine compounds, cyanuric acid compounds, and isocyanuric acid compounds are preferred.
[0108] Examples of the triazine compound include melamine, acetoguanamine, benzoguanamine, melon, melam, succinylguanamine, ethylenebismelamine, polyphosphate melamine, triguanamine, and the like. Examples include aminotriazine compounds such as guanidinomelamine sulfate, melem sulfate, and melam sulfate, the aminotriazine-modified phenolic resins, and compounds obtained by further modifying the aminotriazine-modified phenolic resins with tung oil, isomerized linseed oil, and the like.
[0109] Specific examples of the cyanuric acid compound include cyanuric acid and melamine cyanurate.
[0110] The amount of the nitrogen flame retardant is appropriately selected depending on the type of the nitrogen flame retardant, other components of the curable composition, and the desired degree of flame retardancy. For example, the amount is preferably in the range of 0.05 to 10 parts by mass, and particularly preferably in the range of 0.1 to 5 parts by mass, relative to 100 parts by mass of the total resin component of the curable composition.
[0111] When the above-mentioned nitrogen-based flame retardant is used, a metal hydroxide, a molybdenum compound, or the like may be used in combination.
[0112] As the silicone-based flame retardant, any organic compound containing a silicon atom can be used without particular limitation, and examples thereof include silicone oil, silicone rubber, and silicone resin.
[0113] The amount of the silicone flame retardant is appropriately selected according to the type of silicone flame retardant, other components of the curable composition, and the desired degree of flame retardancy. For example, it is preferably in the range of 0.05 to 20 parts by mass relative to 100 parts by mass of the resin component of the curable composition. In addition, when the silicone flame retardant is used, a molybdenum compound, aluminum oxide, etc. may be used in combination.
[0114] Examples of the inorganic flame retardant include metal hydroxides, metal oxides, metal carbonate compounds, metal powders, boron compounds, and low-melting-point glass.
[0115] Specific examples of the metal hydroxide include aluminum hydroxide, magnesium hydroxide, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, and zirconium hydroxide.
[0116] Specific examples of the metal oxides include zinc molybdate, molybdenum trioxide, zinc stannate, tin oxide, aluminum oxide, iron oxide, titanium oxide, manganese oxide, zirconium oxide, zinc oxide, molybdenum oxide, cobalt oxide, bismuth oxide, chromium oxide, nickel oxide, copper oxide, and tungsten oxide.
[0117] Specific examples of the metal carbonate compound include zinc carbonate, magnesium carbonate, calcium carbonate, barium carbonate, basic magnesium carbonate, aluminum carbonate, iron carbonate, cobalt carbonate, and titanium carbonate.
[0118] Specific examples of the metal powder include aluminum, iron, titanium, manganese, zinc, molybdenum, cobalt, bismuth, chromium, nickel, copper, tungsten, and tin.
[0119] Specific examples of the boron compound include zinc borate, zinc metaborate, barium metaborate, boric acid, and borax.
[0120] Specific examples of the above-mentioned low-melting-point glass include glassy compounds such as Shipuri (Bokusui Brown Company), hydrated glass SiO2-MgO-H2O, PbO-B2O3 system, ZnO-P2O5-MgO system, P2O5-B2O3-PbO-MgO system, P-Sn-OF system, PbO-V2O5-TeO2 system, Al2O3-H2O system, and lead borosilicate system.
[0121] The amount of the inorganic flame retardant is appropriately selected according to the type of the inorganic flame retardant, other components of the curable composition, and the desired degree of flame retardancy. For example, it is preferably blended in the range of 0.05 to 20 parts by mass, and particularly preferably in the range of 0.5 to 15 parts by mass, relative to a total of 100 parts by mass of the resin components of the curable composition.
[0122] Examples of the organic metal salt flame retardant include ferrocene, acetylacetone metal complexes, organic metal carbonyl compounds, organic cobalt salt compounds, organic sulfonic acid metal salts, and compounds in which a metal atom is ionically bonded or coordinately bonded to an aromatic compound or a heterocyclic compound.
[0123] The amount of the organic metal salt flame retardant is appropriately selected according to the type of the organic metal salt flame retardant, other components of the curable composition, and the desired degree of flame retardancy. For example, it is preferably blended in a range of 0.005 to 10 parts by mass relative to a total of 100 parts by mass of the resin components of the curable composition.
[0124] Filling material
[0125] The curable composition of the present invention may contain a filler. If the curable composition of the present invention contains a filler, the obtained cured product can express excellent mechanical properties.
[0126] As filler materials, for example, titanium oxide, glass beads, glass flakes, glass fibers, calcium carbonate, barium carbonate, calcium sulfate, barium sulfate, potassium titanate, aluminum borate, magnesium borate, fused silica, crystalline silica, aluminum oxide, silicon nitride, aluminum hydroxide, kenaf fiber, carbon fiber, alumina fiber, quartz fiber and other fibrous reinforcing agents, non-fibrous reinforcing agents and the like can be cited. They can be used alone or in combination of two or more. In addition, they can also be coated with organic matter, inorganic matter and the like.
[0127] In addition, when glass fiber is used as a filling material, it can be selected from long fiber type roving, short fiber type chopped strands, milled fibers, etc. Glass fiber preferably uses surface-treated glass fiber for the resin used. By matching the filling material, the strength of the non-combustible layer (or carbonized layer) generated during combustion can be further improved. The non-combustible layer (or carbonized layer) once generated during combustion becomes difficult to break, can exert a stable insulation ability, and can obtain a greater flame retardant effect. In addition, it is also possible to give the material high rigidity.
[0128] ·additive
[0129] The curable composition of the present invention may contain additives. If the curable composition of the present invention contains additives, other properties such as rigidity and dimensional stability of the obtained cured product are improved. As additives, for example, stabilizers such as plasticizers, antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, conductivity imparting agents, stress relaxants, mold release agents, crystallization accelerators, hydrolysis inhibitors, lubricants, impact imparting agents, slip modifiers, compatibilizers, nucleating agents, reinforcing agents, reinforcing agents, flow regulators, dyes, sensitizing materials, coloring pigments, rubber polymers, thickeners, anti-settling agents, anti-sagging agents, defoamers, coupling agents, rust inhibitors, antibacterial and antifungal agents, antifouling agents, conductive polymers, etc. may also be added.
[0130] Organic solvents
[0131] When a fiber-reinforced resin molded article is produced by a filament winding method, the curable composition of the present invention may contain an organic solvent. Examples of the organic solvent that can be used include methyl ethyl ketone, acetone, dimethylformamide, methyl isobutyl ketone, methoxypropanol, cyclohexanone, methyl cellosolve, ethyl diglycol acetate, and propylene glycol monomethyl ether acetate. The selection and appropriate amount of the organic solvent can be appropriately selected according to the intended use.
[0132] The curable composition of the present invention has the characteristics of very high curing speed, excellent heat resistance and mechanical strength of the cured product, and can be used for various applications such as coatings, electrical and electronic materials, adhesives, and molded products. In addition to being suitable for use in applications where the curable composition of the present invention is cured itself, it can also be suitable for fiber-reinforced composite materials, fiber-reinforced resin molded products, etc. These are described below.
[0133] Cured product of curable composition
[0134] As a method for obtaining a cured product from the curable composition of the present invention, it is sufficient to follow the curing method of a common epoxy resin composition, and for example, the heating temperature conditions can be appropriately selected according to the type of the combined curing agent, the purpose, etc. For example, a method of heating the curable composition at a temperature range of about room temperature to about 250° C. A molding method, etc., can also use a common method for a curable composition, and in particular, the curable composition of the present invention does not require special conditions.
[0135] Fiber reinforced composite materials
[0136] The fiber reinforced composite material of the present invention refers to a material in a state before curing after the curable composition is impregnated into the reinforcing fiber. Here, the reinforcing fiber can be any of twisted yarn, untwisted yarn, or untwisted yarn, etc., and untwisted yarn and untwisted yarn have excellent formability in the fiber reinforced composite material, so they are preferred. In addition, the form of the reinforcing fiber can use fibers and fabrics formed by aligning the fiber direction in one direction. In the fabric, it can be freely selected from plain weave fabrics, satin fabrics, etc. according to the used part and purpose. Specifically, from the aspect of excellent mechanical strength and durability, carbon fiber, glass fiber, aramid fiber, boron fiber, aluminum oxide fiber, silicon carbide fiber, etc. can be cited, and two or more of them can also be used in combination. Among them, especially from the aspect of good strength of the molded product, carbon fiber is preferred, and the carbon fiber can use various carbon fibers such as polyacrylonitrile, asphalt, and rayon.
[0137] The method for obtaining a fiber-reinforced composite material from the curable composition of the present invention is not particularly limited, and examples thereof include a method in which each component constituting the curable composition is uniformly mixed to produce a varnish, and then, unidirectional reinforcing fibers obtained by aligning reinforcing fibers in one direction are impregnated in the varnish obtained above (in the state before curing in the pultrusion method and the filament winding method); a method in which a woven fabric of reinforcing fibers is overlapped and mounted on a concave mold, and then, sealed with a convex mold, a resin is injected, and pressure impregnation is performed (in the state before curing in the RTM method), etc.
[0138] The curable composition of the fiber-reinforced composite material of the present invention does not necessarily need to be impregnated into the interior of the fiber bundle, and the curable composition may be locally present near the surface of the fiber.
[0139] In addition, for the fiber-reinforced composite material of the present invention, the volume content of the reinforcing fibers relative to the total volume of the fiber-reinforced composite material is preferably 40% to 85%, and from the perspective of strength, it is more preferably in the range of 50% to 70%. When the volume content is less than 40%, the content of the curable composition is too much, and the flame retardancy of the obtained cured product is insufficient, or the various properties required for the fiber-reinforced composite material with excellent specific elastic modulus and specific strength cannot be satisfied. In addition, if the volume content exceeds 85%, the adhesion between the reinforcing fibers and the resin composition is sometimes reduced.
[0140] Fiber-reinforced resin molded products
[0141] The fiber-reinforced resin molded product of the present invention refers to a molded product having a cured product of reinforcing fibers and a curable composition, and is obtained by thermally curing a fiber-reinforced composite material. As the fiber-reinforced resin molded product of the present invention, specifically, the volume content of the reinforcing fibers in the fiber-reinforced molded product is preferably in the range of 40% to 85%, and from the viewpoint of strength, it is particularly preferably in the range of 50% to 70%. As such fiber-reinforced resin molded products, for example, automotive parts such as front subframes, rear subframes, front pillars, center pillars, side beams, cross beams, lower longitudinal beams, upper side beams, and transmission shafts, core components of wires and cables, pipe materials for offshore oil fields, rollers and pipe materials for printing presses, robot fork materials, primary structural materials for aircraft, secondary structural materials, etc. can be cited.
[0142] As a method for obtaining a fiber-reinforced molded product from the curable composition of the present invention, there is no particular limitation, and preferably a drawing method (pultrusion method), a fiber winding method, an RTM method, etc. are used. The drawing method (pultrusion method) refers to a method in which a fiber-reinforced composite material is introduced into a mold, heated and cured, and then drawn with a drawing device to form a fiber-reinforced resin molded product. The fiber winding method refers to a method in which a fiber-reinforced composite material (including unidirectional fibers) is rotated while being wound around an aluminum bushing, a plastic bushing, etc., and then heated and cured to form a fiber-reinforced resin molded product. The RTM method refers to a method using two molds, a concave mold and a convex mold, and a fiber-reinforced composite material is heated and cured in the above-mentioned mold to form a fiber-reinforced resin molded product. It should be noted that in the case of forming a large product or a fiber-reinforced resin molded product of a complex shape, the RTM method is preferably used.
[0143] As the molding conditions of the fiber-reinforced resin molded product, it is preferred to heat cure and mold the fiber-reinforced composite material at a temperature range of 50°C to 250°C, and more preferably to mold at a temperature range of 70°C to 220°C. This is because if the molding temperature is too low, sufficient rapid curing may not be obtained, and conversely, if it is too high, it may become easy to cause warping caused by thermal strain. As other molding conditions, there may be a method of curing in two stages, such as pre-curing the fiber-reinforced composite material at 50°C to 100°C to form a non-sticky cured product, and then further treating it at a temperature condition of 120°C to 200°C.
[0144] As other methods for obtaining a fiber-reinforced molded product from the curable composition of the present invention, there can be mentioned: a hand lay-up method and an injection molding method in which a fiber aggregate is laid on a mold and the varnish and the fiber aggregate are gradually stacked in multiple layers; a vacuum bag method in which a base material containing reinforcing fibers is impregnated with the varnish while being stacked and molded using either a male mold or a female mold, and the resulting product is covered with a flexible mold that allows pressure to act on the molded product, airtightly sealed, and vacuum (decompressed) molded; an SMC pressurization method in which a varnish containing reinforcing fibers is formed into a sheet in advance and the resulting product is compression molded using a mold; and the like.
[0145] Example
[0146] Next, the present invention will be specifically described based on Examples and Comparative Examples. In the following, "parts" and "%" are based on mass unless otherwise specified.
[0147] Examples 1 to 16 and Comparative Examples 1 to 4
[0148] The components were blended according to the formulations shown in Tables 1 to 3 below, and stirred and mixed uniformly to obtain curable compositions. The curable compositions were subjected to various evaluation tests in the following manners. The results are shown in Tables 1 to 3.
[0149] In addition, the components used in Examples and Comparative Examples are as follows.
[0150] <Epoxy resin (A)>
[0151] 840S: "EPICLON 840S" manufactured by DIC Co., Ltd.
[0152] Bisphenol A epoxy resin, epoxy equivalent 184g / equivalent
[0153] 830S: "EPICLON 830S" manufactured by DIC Co., Ltd.
[0154] Bisphenol F epoxy resin, epoxy equivalent 168g / equivalent
[0155] S720: SYNASYA "S-720"
[0156] 4,4'-Methylenebis[N,N-diglycidylaniline], epoxy equivalent 118g / equivalent
[0157] EX212L: "Denacol EX212L" manufactured by Nagase Chemte X Co., Ltd.
[0158] 1,6-hexanediol epoxy resin, epoxy equivalent weight 135g / equivalent
[0159] <Amine compounds>
[0160] N-AEP: N-aminoethylpiperazine
[0161] TETA: triethylenetetramine
[0162] 1,3-BAC: 1,3-bis(aminomethyl)cyclohexane
[0163] NBDA: Norbornene diamine
[0164] IPDA: Isophorone diamine
[0165] DETDA: Diethyltoluenediamine
[0166] <Epoxy resin with dispersed core-shell particles>
[0167] MX-153: "カネエースMX-153" manufactured by Kaneka Co., Ltd.
[0168] Bisphenol A epoxy resin dispersed with 33% polybutadiene rubber particles
[0169] MX-257: "カネエースMX-257" manufactured by Kaneka Co., Ltd.
[0170] Bisphenol A epoxy resin dispersed with 37% polybutadiene rubber particles
[0171] MX-136: "カネエースMX-136" manufactured by Kaneka Co., Ltd.
[0172] Bisphenol F epoxy resin dispersed with 25% polybutadiene rubber particles
[0173] <Other resins>
[0174] PVF: "VINYLEC K" polyvinyl formal resin manufactured by JNC Corporation
[0175] <Measurement of Viscosity>
[0176] The viscosity at 25° C. in a state where a substance other than the amine compound was blended was measured using an E-type viscometer “TV-20” (manufactured by Toki Sangyo Co., Ltd.).
[0177] <Determination of Glass Transition Temperature>
[0178] The previously obtained curable composition was poured into a mold box with a thickness of 2 mm and heated at 120°C for 5 minutes. The obtained cured product was cut into a width of 5 mm and a length of 50 mm with a diamond tool and used as a test piece. Next, the dynamic viscoelasticity based on double-sided bending of the test piece was measured using a viscoelasticity measuring device ("DMS6100" manufactured by SII Nano Technology), and the temperature at which tanδ becomes the maximum value was evaluated as the glass transition temperature (Tg). It should be noted that the measurement conditions for the dynamic viscoelasticity measurement are set to temperature conditions of room temperature to 260°C, a heating rate of 3°C / min, a frequency of 1Hz, and a strain amplitude of 10μm.
[0179] <Determination of fracture toughness>
[0180] The cured product obtained above was used to measure K according to ASTM D 5045-99. IC The value of .
[0181] <Determination of tensile strength and elongation>
[0182] The cured product obtained above was used to measure the tensile strength using a precision universal testing machine ("AUTOGRAPH AG-1" manufactured by Shimadzu Corporation) in accordance with JIS K7161.
[0183] <Determination of Gel Time>
[0184] After mixing the components in the ratio shown in Table 2, 0.15 g of the curable composition was immediately placed on a hot plate heated to 100° C. and the time (seconds) until the composition became gel was measured while stirring with a spatula. This operation was repeated three times and the average value was used for evaluation.
[0185] A: Less than 300 seconds
[0186] B: 300 to 600 seconds
[0187] C: More than 600 seconds
[0188] [Table 1]
[0189]
[0190] [Table 2]
[0191]
[0192] [Table 3]
[0193]
Claims
1. A fiber-reinforced composite material comprising reinforcing fibers and a curable composition impregnated into the reinforcing fibers as essential components, The curable composition comprises an epoxy resin (A), an amine compound (B) and core-shell particles (C), wherein the amine compound (B) contains an N-(aminoalkyl)piperazine compound (B1) as an essential component. The core-shell particles (C) are composed of a core and a shell, and the polymer constituting the core has properties as a rubber. The content of the core-shell particles (C) is in the range of 0.5% by mass to 10% by mass relative to the total mass of the epoxy resin (A), the amine compound (B) and the core-shell particles (C). The epoxy equivalent of the epoxy resin (A) is in the range of 165 g / eq to 190 g / eq, and the viscosity at 25° C. is in the range of 2000 mPa·s to 11000 mPa·s.
2. The fiber-reinforced composite material according to claim 1, wherein: The epoxy resin (A) contains a bisphenol epoxy resin (A1) as an essential component.
3. The fiber-reinforced composite material according to claim 1 or 2, wherein: The ratio of the N-(aminoalkyl)piperazine compound (B1) to the total mass of the amine compound (B) is in the range of 20% by mass to 80% by mass.
4. The fiber-reinforced composite material according to claim 1 or 2, wherein: The core-shell particles (C) are copolymers composed of a core portion and a shell layer, wherein the shell layer includes a second polymer graft-polymerized to the core portion.
5. The fiber-reinforced composite material according to claim 4, wherein: The polymer and / or the second polymer constituting the core portion is a copolymer.
6. The fiber-reinforced composite material according to claim 1 or 2, wherein: The core-shell particles (C) are dispersed in the epoxy resin (A) in the form of primary particles with an average particle size in the range of 30 nm to 1000 nm. 7 . A fiber-reinforced resin molded product obtained by thermally curing the fiber-reinforced composite material according to claim 1 .
8. A method for producing a fiber-reinforced resin molded product, wherein: The fiber-reinforced composite material according to any one of claims 1 to 6 is thermally cured.
Citation Information
Patent Citations
Carbon fiber reinforced composite material and method for producing the same
JP2010059300A
Rubber-modified epoxy compounds
US4778851A
Wear-resistant epoxy glue and preparation method thereof
CN102040933A
Curable epoxy resin systems containing mixtures of amine hardeners and an excess of epoxide groups
CN103619900A
Structural adhesive and bonding application thereof
CN103797043A
